Enabling the Angstrom Era: 2D material-based multi-bridge-channel complementary field effect transistors - Hoon Hahn Yoon; Jin Young Park; Yonas Tsegaye Megra; Ju Hwan Baek; Minuk Song; Deji Akinwande; Daewon Ha; Dong-Ho Kang; Hyeon-Jin Shin (npj 2D Materials and Applications)
Abstract This review presents a strategic roadmap for integrating two-dimensional materials (2DMs) into multi-bridge channel (MBC) complementary field-effect transistors (CFETs). It highlights key integration challenges, essential design considerations, and industrialization strategies for 2DM-MBC CFETs. These advances are expected to enable ultra-small, energy-efficient, and high-performance devices in the Angstrom Era that transcend the scaling limitations of silicon technology, paving the way for innovative applications in artificial intelligence (AI), the Internet of Things (IoT), and edge computing.